Cathepsin D overexpressed by cancer cells can enhance apoptosis-dependent chemo-sensitivity independently of its catalytic activity - Beaujouin, Mélanie (Kluwer Academic/Plenum Publishers, 2008)
The aspartic protease cathepsin D (cath-D) is a key mediator of induced-apoptosis and its proteolytic activity has been generally involved in this event. During apoptosis, cath-D is translocated to the cytosol. Since cath-D is one of the lysosomal enzymes which requires a more acidic pH to be proteolytically-active relative to the cysteine lysosomal enzymes such as cath-B and -L, it is therefore open to question whether cytosolic cath-D might be able to cleave substrate(s) implicated in the apoptotic cascade. Here we have investigated the role of wild-type cath-D and its proteolytically-inactive counterpart over-expressed by 3Y1-Ad12 cancer cells during chemotherapeutic-induced cytotoxicity and apoptosis, as well as the relevance of cath-D catalytic function. We demonstrate that wild-type or mutated catalytically-inactive cath-D strongly enhances chemo-sensitivity and apoptotic response to etoposide. Both wild-type and mutated inactive cath-D are translocated to the cytosol, increasing the release of cytochrome c, the activation of caspases-9 and -3 and the induction of a caspase-dependent apoptosis. In addition, pre-treatment of cells with the aspartic protease inhibitor, pepstatin A, does not prevent apoptosis. Interestingly therefore, the stimulatory effect of cath-D on cell death is independent of its catalytic activity. Overall, our results imply that cytosolic cath-D stimulates apoptotic pathways by interacting with a member of the apoptotic machinery rather than by cleaving specific substrate(s).